Entrepreneurship Education Model through Vocational Skills: A Case Study on Manba'ul Hikmah and Al-Musyaffa' Islamic Boarding Schools, Kendal - Rohman, Basyar; Ali, Mudzakkir; Hamzah, Ghufron (EDUKASIA Jurnal Pendidikan dan Pembelajaran, 2024)
This study aims to analyze the implementation of the entrepreneurship education model through vocational skills at Manba'ul Hikmah and Al Musyaffa' Islamic Boarding Schools in Kendal Regency, focusing on the reasons for its implementation, the process, and the results achieved. The research is based on the important role of Islamic boarding schools in developing students’ religious knowledge, practical skills, and moral character to address the challenges of Society 5.0 and the Industrial Revolution 4.0. A qualitative approach was used with a case study design and a comparative descriptive method. Data were collected through observation, unstructured interviews, and documentation, with purposive sampling applied to select informants. The findings show that the entrepreneurship education model at both boarding schools successfully equips students with vocational and entrepreneurial skills such as agriculture, crafts, digital technology, culinary arts, and business management. Students become more economically independent, capable of managing school business units, and contribute to community economic empowerment. The program also enhances the operational efficiency of the institutions and integrates Islamic values into practical learning. Overall, this integrative entrepreneurship education model effectively prepares students for the workforce, fosters independence, and strengthens institutional sustainability. It can serve as a practical reference for other Islamic boarding schools seeking to develop students’ competencies in line with modern economic and technological demands while maintaining strong Islamic values